Relasi Keluarga dalam Surah Ṭāhā ayat 29–32: Analisis Komparatif Tafsīr al-Ṭabarī dan Tafsīr al-Munīr - Zubeir Batubara (Yayasan Albahriah Jamiah Indonesia, 2026)
The study of family relations in the Quran has conceptual significance because the family verses not only represent personal relationships, but also contain constructions of authority, social ethics, and cooperation patterns that impact the formation of social order. Surah Ṭāhā verses 29–32, which record the Prophet Moses’ request regarding Aaron’s role as a companion and strengthener of the mission, becomes an important locus for reading the differences in classical and contemporary interpretive approaches in interpreting family relations. The purpose of this study is to comparatively analyze the construction of family relations, the distribution of authority, and the dimensions of social ethics in Tafsīr al-Ṭabarī and Tafsīr al-Munīr to identify the shift in interpretive paradigms. The method used is a qualitative study based on a literature study with a comparative analysis approach of interpretations, using Tafsīr al-Ṭabarī as a representation of classical interpretation based on riwāyah and Tafsīr al-Munīr as a representation of contemporary interpretation that is integrative and contextual. The analysis shows that Tafsīr al-Ṭabarī constructs family relations within the framework of the legitimacy of prophetic authority and functional-instrumental kinship, with an emphasis on the sanad of narration and initial consensus as determinants of meaning. In contrast, Tafsīr al-Munīr constructs family relations as a model of ethical collaboration that emphasizes competence, communication, and social responsibility, so that the relationship between Musa and Harun is understood as a prototype of participatory leadership relevant to the modern social context. This difference reflects the epistemological transformation from normative-historical interpretation to normative-contextual interpretation, while also confirming the contribution of this study to the development of Quranic exegesis studies in reading family verses dynamically and in layers.